Contrasting internet adoption in early and advanced old age: does internet self-efficacy matter? - Jokisch, Mario; Scheling, Louisa; Doh, Michael; Wahl, Hans-Werner (The journals of gerontology. Series B, Psychological sciences, social sciences, 2022)
Understanding why older adults (including those in very old age) use or do not use the Internet can build on the technology acceptance model (TAM). In this cross-sectional study, we translate the TAM to the Internet and assume that perceived usefulness of the Internet (PUI) and perceived ease of use of the Internet (PEUI) will be revealed as major predictors of behavioral intention to use the Internet (BII). Additionally, we consider the role of Internet self-efficacy (ISE) as another major factor for older adults’ Internet use. We also argue that life phase, particularly early as opposed to advanced old age, may moderate how PUI, PEUI, and ISE relate to BII.A sample of 1,200 older adults aged 60 years and older (60-74 years, n = 658; 75-99 years, n = 542) was randomly drawn from the city of Stuttgart, Germany. Sociodemographic variables and major indicators of TAM and ISE were assessed based on a computer-assisted telephone interviewing procedure.Latent structural equation modeling revealed that PUI is the more important predictor of BII in older adults. Furthermore, ISE revealed statistically meaningful positive links with PUI, PEUI, and BII. Multigroup comparison revealed that PUI had a stronger linkage with BII in early old age, whereas ISE was more important for BII in advanced old age.The results suggest that ISE may enrich the network of TAM constructs among older adults in general but specifically in advanced old age.